Pengaruh NPL Dan LDR Terhadap Profitability Perusahaan Perbankan Dengan CAR Sebagai Mediasi - Silvia Chandrawati Susoni Basri, Elizabeth Sugiarto Dermawan (Jurnal Ekonomi, 2021)
This study aims to obtain empirical evidence regarding the effect of NPL and LDR on profitability through CAR as intervening variable. Profitability is proxied by ROA. Purposive sampling technique is used to collect data. This study uses data from 27 banking companies listed on the Indonesian Stock Exchange from 2018-2020 with total 81 data. The analysis technique used is path analysis and data are processed with SPSS 17. The result of data analysis found that NPL and LDR have negative insignificant effect on CAR. NPL indicates it has a negative significant effect on profitability. Meanwhile, LDR has a positive insignificant effect on profitability and CAR has a positive significant effect on profitability. Based on the result of path analysis, CAR cannot mediate the effect of NPL and LDR on profitability.